Gainfully employing descending controls in acute and chronic pain management - White, Kate; Targett, Mike; Harris, John (Elsevier, 2018)
Specific primary afferent fibres termed nociceptors are responsible for transmitting nociceptive information. Centrally the axonal terminals of these fibres synapse with secondary projection neurones in the spinal dorsal horn to transmit nociceptive information to the higher centres in the brain. Irrespective of the presence or absence of nociceptive inflow the activity of dorsal horn neurones is modulated by, amongst other things, local interneurones and descending midbrain and brainstem networks which can inhibit or facilitate dorsal horn transmission. These pathways therefore set the threshold for information inflow to the CNS. This review article summarises the anatomy, physiology and pharmacology particularly of these descending inhibitory and facilitatory pathways and explains why the study of descending modulation is essential if we are to develop more efficacious interventions for treating pain and relieving suffering.